국내 생산자 물가와 수입 물가가 우리나라 농산물 소비자 물가에 미치는 비선형 관계 분석 - 석준호; Seok Jun-ho (농촌경제, 2025)
본 연구는 국내 농산물 생산자 물가지수와 수입 물가지수가 농산물 소비자 물가지수에 미치는 영향을 2004년 4월부터 2024년 12월까지의 월별자료를 활용하여 분석을 진행하였다. 선형 및 Quantile Autoregressive Distributed Lag 모형을 활용하여 국내 농산물 생산자 물가지수와 수입 물가지수가 농산물 소비자 물가지수에 미치는 장단기, 선형 및 비선형 영향에 대한 분석을 시행하였다. 분석 결과 국내 농산물 생산자 물가지수, 수입 물가지수, 농산물 소비자 물가지수 간에는 장기적 균형관계가 존재하고 국내 농산물 생산자 물가지수가 농산물 소비자 물가지수에 미치는 영향력은 수입 물가지수에 비해 큰 것으로 나타났다. 또한 장기에 70분위 이상의 시기에서 국내 농산물 생산자 물가지수에 장기에 농산물 소비자 물가지수에 미치는 한계 효과는 분위가 증가함에 따라 감소하지만, 수입 물가지수가 농산물 소비자 물가지수에 미치는 한계 효과는 분위가 증가함에 증가하는 것으로 나타났다. 하지만 한계 효과의 절대적인 크기는 농산물 생산자 물가지수가 더 큰 것으로 나타났다. 이와 같은 결과는 우리나라 농산물 소비자 물가를 안정적으로 관리하기 위해서는 우리나라 농산물 생산자 물가지수를 안정적으로 관리하는 것이 중요하다는 의미이다. This study investigates the effects of the agricultural producer and agricultural import price indices on the agricultural consumer price index in Korea using monthly data from April 2004 to December 2024. Using linear and quantile autoregressive distributed lag models, the effects of the domestic agricultural producer price and import price indices on the agricultural consumer price index was studied in terms of short-run, long-run, linear, and non-linear effects. Our results show a long-run relationship between the agricultural producer price, import price, and consumer price indices. The effect of the domestic agricultural producer price index on the agricultural consumer price index is greater than that of the agricultural import price index. While the marginal effect, greater than or equal to the 70th quantile, of the agricultural producer price index on the agricultural consumer price index has an increasing trend with quantiles, that of the agricultural import price index on the agricultural consumer price index has a decreasing trend with quantiles. However, the absolute size of the marginal effect is greater for the agricultural producer price index. These results imply that a stable domestic agricultural producer price index is important to control the agricultural consumer price index.